Crystallization and preliminary X‐ray diffraction analysis of the Cmr2–Cmr3 subcomplex in the CRISPR–Cas RNA‐silencing effector complex. Issue 5 (22nd May 2013) - Osawa, Takuo; Inanaga, Hideko; Numata, Tomoyuki
<x xml:space="preserve">Abstract</x> Clustered, regularly interspaced, short palindromic repeat (CRISPR) loci, found in prokaryotes, are transcribed to produce CRISPR RNAs (crRNAs). The Cmr proteins (Cmr1–6) and crRNA form a ribonucleoprotein complex that degrades target RNAs derived from invading genetic elements. Cmr2dHD, a Cmr2 variant lacking the N‐terminal putative HD nuclease domain, and Cmr3 were co‐expressed in Escherichia coli cells and co‐purified as a complex. The Cmr2dHD–Cmr3 complex was co‐crystallized with 3′‐AMP by the vapour‐diffusion method. The crystals diffracted to 2.6 Å resolution using synchrotron radiation at the Photon Factory. The crystals belonged to the orthorhombic space group I222, with unit‐cell parameters a = 103.9, b = 136.7, c = 192.0 Å. The asymmetric unit of the crystals is expected to contain one Cmr2dHD–Cmr3 complex with a Matthews coefficient of 3.0 Å3 Da−1 and a solvent content of 59%.